REHABILITASI DAN GANTI KERUGIAN TERDAKWA YANG DIADILI TANPA BERDASARKAN UNDANG-UNDANG - Cahyono, Rudi (JUSTNESS - Jurnal Hukun dan Agama, 2022)
Abstract   Rehabilitation is the restoration of a person's rights in the original ability or position given by the court. In practice, compensation in criminal law can be requested for 2 things, namely: because of the actions of law enforcement officials and because of the actions of the defendant. Compensation is a person's right to obtain fulfillment of his demands in the form of compensation for a sum of money because he is arrested, detained, prosecuted or tried without any reason based on the applicable law or because of an error regarding the person or the law he applies Data collected through several references, reading books, which is then processed by several stages, namely editing, namely re-examination of all data that has been obtained. Organizing, namely compiling and systematizing the data that has been obtained, and analyzing, namely analyzing the data that has been collected, using the Descriptive Analysis Method. Furthermore, it concludes and is analyzed from the point of view of positive law in Indonesia.   Keywords: Rehabilitation, Compensation